FEATURES OF THE MAIN INDICATORS OF THE PHYSICAL DEVELOPMENT OF TEENAGERS IN THE TOMSK REGION - I. A. Deyev; I. L. Kolomeyets; Ye. M. Kamaltynova; Ye. S. Kulikov; A. N. Levko; O. S. Fyodorova; K. V. Kulikova; V. I. Yurkova (Бюллетень сибирской медицины)
Objective. To study the physical growth and development of adolescents (aged 13–16 years) living in the Tomsk region. Material and Methods. This study is a framework (№299 from 18.07.2011) of the Department of Health Care of Tomsk region, we analyzed the results of medical examinations of adolescents (n = 7120, average age 13.98 ± 0.04, 49.87% – boys). Measurements of height and weight, the circumference of the chest and head (data rounded to 0.1 kg and 0.1 cm, respectively) are taken. The body mass index (BMI) is calculated as the ratio of weight (kg) / height2 (m2). Statistical analysis was performed using the software package Statistica for Windows 10.0 and the software StatCalc 6.0.Results. Average height of adolescents is (163.10 ± 0.09) cm. On Average boys are taller than girls ((165.34 ± 0.15) cm and (160.87 ± 0.11) cm, p < 0.001). The body weight is (53.99 ± 0.13) kg (boys – (55.28 ± 0.20) kg, girls – (52.72 ± 0.17) kg, p < 0.001). Boys chest circumference is (79.26 ± 0.30) cm, girls is (79.99 ± 0.13) cm, head circumference are (55.43 ± 0.07) cm and (54.77 ± 0.04) cm, respectively (p < 0.01). The results show difference between Tomsk boys and rest of the Russia Federation. The average BMI is (20.20 ± 0.04) kg/m2 (girls – (20.32 ± 0.07), boys – (20.08 ± 0.06) kg/m2). The urban lifestyle in Tomsk Region leads to boys obesity.Conclusion. The study revealed the regional physical growth and development characteristics. Anthropometric data in Tomsk region adolescents are higher than the same data in RF.